Our Pachao [our rice terraces] : a theory-based documentary on the rice terraces of Batad, Ifugao - Batard, Emilie (College of Mass Communication, University of the Philippines Diliman, 2013)
"The documentary film Our Pachao (Our Rice Terraces) presents the current situation in Batad at a time where modernization has already affected traditional way of living in the village. It also aims to understand the reasons why the community is facing challenges in balancing modernity and conversation of their cultural heritage. The term traditional regulation implies the notion of rules and a way of living with each other within a community. Our Pachao is an anthropologically minded film that voices out the testimonials of Batad people from different backgrounds and positions within the community. They express their thoughts on economics, tourism, out-migration, education, livelihood and sustainability along with a scientific approach from a professor in anthropology. The common understanding of the word modernization is that it is the accepting or adopting of modern ways, ideas, or style. In the case of Batad and its inhabitants, their coming to terms with modernization is one that is functional because the modern ways that they have chosen to adopt have allowed them to have better access to money transactions, media and technology that makes daily life easier. It has allowed them to buy everyday goods such as rice and has given them access to information through media in television. For the inhabitants of Batad, adopting modern ways has also somehow influenced how they view their own culture. The younger generations' exposure to influences coming from the media and peers has had an effect on their lifestyle choices."